Wealth generation: How to boost income mobility in the UK - Justin Callais; Vincent Geloso (Institute of Economic Affairs (IEA), 2024)
Many argue that income mobility is declining. This applies to all types of income mobility (relative and absolute; intergenerational and intragenerational). As remedies, those who worry and others who want to improve mobility tend to propose expansions to welfare programmes. We argue that economic freedom (i.e., safer property rights, less regulated markets, lower taxation and open trade) is far more potent to improve income mobility than redistributive policies. There is a direct effect of economic freedom by removing legal hurdles to work. There is also an indirect effect by promoting economic growth in ways that are biased towards the poor. There is new international evidence suggesting that economic freedom promotes intergenerational absolute and relative income mobility. There is rich subnational data from Canada showing that economic freedom promotes intragenerational income mobility (relative and absolute). There is indirect evidence from economic history, economic geography and the economics of occupational licensing confirming the above results. The UK is a middling country in terms of both income mobility and occupational licensing laws. We highlight two main areas of reform to promote economic freedom to increase the UK's performance in mobility: deregulation in occupational licensing laws and housing restrictions.
Keywords: 330; Social mobility; Income distribution; Great Britain; Economic liberalism; Soziale Mobilität; Einkommensverteilung; Großbritannien; Wirtschaftsliberalismus